Effectiveness of portable electronic and optical magnifiers for near vision activities in low vision: a randomised crossover trial. (12th May 2017) - Taylor, John J.; Bambrick, Rachel; Brand, Andrew; Bray, Nathan; Dutton, Michelle; Harper, Robert A.; Hoare, Zoe; Ryan, Barbara; Edwards, Rhiannon T.; Waterman, Heather; Dickinson, Christine
Abstract: Purpose: To compare the performance of near vision activities using additional portable electronic vision enhancement systems (p‐EVES), to using optical magnifiers alone, by individuals with visual impairment. Methods: A total of 100 experienced optical aid users were recruited from low vision clinics at Manchester Royal Eye Hospital, Manchester, UK, to a prospective two‐arm cross‐over randomised controlled trial. Reading, performance of near vision activities, and device usage were evaluated at baseline; and at the end of each study arm (Intervention A: existing optical aids plus p‐EVES; Intervention B: optical aids only) which was after 2 and 4 months. Results: A total of 82 participants completed the study. Overall, maximum reading speed for high contrast sentences was not statistically significantly different for optical aids and p‐EVES, although the critical print size and threshold print size which could be accessed with p‐EVES were statistically significantly smaller ( p < 0.001 in both cases). The optical aids were used for a larger number of tasks ( p < 0.001), and used more frequently ( p < 0.001). However p‐EVES were preferred for leisure reading by 70% of participants, and allowed longer duration of reading ( p < 0.001). During the study arm when they had a p‐EVES device, participants were able to carry out more tasks independently ( p < 0.001), and reported less difficulty with a range of near vision activities ( p < 0.001). Conclusions: The study provides evidence that p‐EVES devices can play a useful role in supplementing the range of low vision aids used to reduce activity limitation for near vision tasks.